Patterns of Interaction in a Computer Conference Transcript - Fahy, Patrick J.; Crawford, Gail; Ally, Mohamed (International Review of Research in Open and Distributed Learning, 2001)
An analysis of the interaction patterns in an online conference from a distance education graduate course was conducted, using an approach that focused on the transcript's interactional and structural features. A new tool for transcript analysis, the TAT (Transcript Analysis Tool), was used to analyze interactional features, while structural elements suggested by social network theory were examined. Analysis of the patterns of interaction in the conference showed interaction was variable, and that while all participants were engaged, intensity and persistence of participation were unequal among individual participants in several ways. The TAT showed the proportions of five major types of sentences in the transcript, corresponding to different modes of interaction (questions, statements, reflections, engaging comments, and quotations/citations). The findings showed that the TAT seemed to relate usefully to other work in this area, and that social network principles were valuable in the analysis of conference interaction.